Pre fraud: some firms' charateristics - Puat Nelson, Sherliza (2012)
The paper specifically examines the pre fraud firms’ characteristics for over 3 years before fraud occurred. Selections of companies were made from Securities Commissions’ enforcement actions released between the years 2000 until 2008. A matched pair sampling was made with the control group, and 192 firms’ observations were made. Findings revealed that there were decreased in cash flow as well as lesser number of board sizes during the three years before the fraud for fraud firms. In addition, roles of independent directors may lessen the impact of fraud.